Demo: FocusVR: Effective & Usable VR Display Power Management - Wee, Tian Kat; Cuervo, Eduardo; Balan, Rajesh (MobiSys'16, 2016)
We will demo FocusVR, a system for effectively and efficiently reducing the power consumption on Virtual Reality (VR) headset with OLED displays. FocusVR smartly dims the screen to reduce display power through the use vignette on VR displays. Our approach has shown to save up to 80% of display power with no impact to usability and task completion time on the Samsung Galaxy Gear VR, Oculus Rift and HTC Vive (paper under review). In this demo, we will demonstrate the technique on a Samsung Galaxy Gear VR with a Samsung Galaxy Note 4. During the demo, users will be able to observe the power saving technique within a virtual world in two modes: fly-through and interactive.